From Absolution to Action: Examining Americans' Reactions to High‐Profile Corporate Scandals . Issue 1 (9th February 2020) - Guckian, Meaghan L.; Chapman, Daniel A.; Lickel, Brian; Markowitz, Ezra M.
Abstract: When corporations behave inappropriately, for example, by intentionally circumventing emissions regulation or jacking up the price of a life‐saving drug, assessing and assigning culpability is both natural and necessary. Such ascriptions of blame influence how consumers perceive and engage with corporations in the wake of misconduct. In a nationally representative sample of American adults, we examined how people's mental models of corporate wrongdoing influenced their awareness of and responses to a series of corporate scandals that broke between 2015 and 2017. Using a mixed effects modeling approach addressing both individual and scandal‐level variability, our results revealed that subscribing to the belief that corporate scandals are the product of the corporate culture (as opposed to the actions of a "few bad apples" within an organization) amplified people's awareness of, degree of concern about, and the probability of having taken action against transgressing corporations. The findings presented here highlight the importance of exploring consumers' complex responses to corporate scandals, particularly for regulators and consumer advocates interested in leveraging public outcry to hold corporations responsible.